Sociology of globalisation : perspectives from India - Somayaji, Sakarama; Somayaji, Ganesha (Jaipur : Rawat Publications, 2006)
Contributed articles.
Includes bibliographical references and index.
Keywords: GLOBALIZATION -- SOCIAL ASPECTS -- INDIA; Globalization -- ECONOMIC ASPECTS -- INDIA